Potato (Solanum tuberosum L.) cv. Nevskij microtuber formation features in in vitro culture - A.T. Gizatullina; Z. Stasevski; E.A. Gimaeva; G.F. Safiullina (Учёные записки Казанского университета: Серия Естественные науки)
The process of tuber formation in potato depends on many factors: genotype, exogenous hormones, photoperiod, source and concentration of carbohydrate. This work aims to study microtuber formation in potato (Solanum tuberosum L.) cv. Nevskij cultured in vitro. The plants were cultivated on the Murashige and Skoog medium. We compared the effects of sucrose (30, 50, 60 and 80 g/L), kinetin (1, 1.75, and 2.5 mg/ L), and benzylaminopurine (BAP) (1, 3, 5, and 8 mg/L) in background sucrose 80 g/L under the conditions of short days (8/16 h, SD) and continuous darkness (0/24 h, CD). Potato explants planted on the experimental culture media were cultivated for the first 2 weeks under the long-day conditions (16/8 h, LD). At the next stage, the explants were cultivated within 10 weeks under the short-day SD and CD conditions. The growth and development of microtubers were observed. The morphometric parameters of the obtained microtubers by the end of the 12th week were evaluated. On the cultural medium containing 80 g/L sucrose, the number of microtubers larger than 5 mm increased under the conditions of SD from 20% to 56% compared with CD. Under the CD conditions, an increase in the yield of tubers larger than 5 mm, as compared with the hormone-free nutrient medium (80 g/L sucrose), was promoted by adding kinetin (1 and 2.5 mg/L) and BAP (5 mg/L) to the nutrient medium.